A high-performance sodium anode composed of few-layer MoSe2 and N, P doped reduced graphene oxide composites. Issue 9 (24th July 2018) - Roy, Amlan; Ghosh, Arnab; Kumar, Ajit; Mitra, Sagar
Abstract : Capacity and stability enhancement has been observed for MoSe2 covered with N, P-doped rGO sheets. The sodiation behaviour was also investigated through different ex situ studies. Abstract : The renewable energy revolution and its practical applications demand the need for large solar storage options. Lithium-ion batteries may remain top in terms of their utilization and performance, however their cost-per-kWh impacts their usage, and researchers prefer to stick to sodium-ion chemistry as a large storage option. One of the main research topics for rechargeable sodium-ion batteries is in proposing new anodes, since the commercial graphite anode is incompatible for use in SIBs as its larger radius (0.98 Å vs. 0.69 Å of Li + ) leads to sluggish Na-ion transport during the cycling process. Our team is continuously working on the development of chalcogenide-based anodes for use in sodium-ion batteries and their reaction mechanisms. In this work, we prepared MoSe2 and MoSe2 -N, P-doped rGO composites (with the latter denoted as MoSe2 /NPr) as active anodes for use in sodium-ion batteries. The morphology and electrochemical properties of MoSe2 /NPr were characterised and compared with those of the bare MoSe2 electrode. The MoSe2 /NPr composite delivers a capacity of 337 mA h g −1 at 0.1 A g −1 after 100 cycles and 244.4 mA h g −1 at 1 A g −1 ; these values are higher than those of MoSe2 /rGO (225.6 mA h g −1 at 0.1 A g −1 ) and MoSe2 electrodes (206 mA h g −1 at 0.1 A g −1 ). The excellent performance of MoSe2 /NPr is attributed to the interconnected doped rGO sheets that provide sufficient active sites for MoSe2 with improved conductivity and reduced volume expansion during the cycling process. In addition, the sodium storage mechanism is investigated by several ex situ physical and microscopic studies.